Modeling ionized gas in low-metallicity environments: the Local Group dwarf galaxy IC 10 - Polles, Fiorella L.; Hony, Sacha; Chevance, Mélanie (Astronomy and astrophysics, 2019)
Context. Star formation activity is an important driver of galaxy evolution and is influenced by the physical properties of the interstellar medium. Dwarf galaxies allow us to understand how the propagation of radiation and the physical conditions of the different ISM phases are affected by the low-metallicity environment. Aims. Our objective is to investigate the physical properties of the ionized gas of the low-metallicity dwarf galaxy, IC 10, at various spatial scales: from individual HII regions to the entire galaxy scale and examine whether diagnostics for integrated measurements introduce bias in the results. Methods. We modeled the ionized gas combining the mid- and far-infrared fine-structure cooling lines observed with Spitzer/IRS and Herschel/PACS, with the photoionization codeCLOUDY. The free parameters of the models are the age of the stellar cluster, the density, and the ionization parameter of the ionized gas as well as the depth of the cloud. The latter is used to investigate the leakage of the ionizing photons from the analyzed regions of IC 10. We investigated HII regions in the main star-forming body, on scales of ~25 pc, three in the main star-forming region in the center of the galaxy and two on the first arc. We then considered larger sizes on the scale of ~200 pc. Results. Most clumps have almost-identical properties, density ~102–102.6 cm−3, ionization parameter between 10−2.2 and 10−1.6, and age of the stellar cluster ~5.5 Myr. All of them are matter-bounded regions, allowing ionizing photons to leak. The relatively uniform physical properties of the clumps suggest a common origin for their star formation activity, which could be related to the feedback from stellar winds or supernovae of a previous generation of stars. The properties derived for ~200 pc size “zones” have similar properties as the HII regions they encompass, but with the larger regions tending to be more radiation bounded. Finally, we investigated the fraction of [CII] 157.7 μm, [SiII] 34.8 μm and [FeII] 25.9 μm emission arising from the ionized gas phase and we find that most of the emission originates from the neutral gas, not from the ionized gas.